Cross-Shaped Adversarial Patch Attack - Ran, Yu; Wang, Weijia; Li, Mingjie; Li, Lin-Cheng; Wang, Yuan-Gen; Li, Jin (IEEE transactions on circuits and systems for video technology, 2024)
Recent studies have shown that deep learning-based classifiers are vulnerable to malicious inputs, i.e., adversarial examples. A practical solution is to construct a perceptible but localized perturbation called patch, making the well-trained models misclassified. However, most existing patch-based adversarial attacks focus on designing patches with localized rectangles, squares, or grids, ignoring the effect of the non-local patch. In this paper, we propose a novel cross-shaped patch attack paradigm (CSPA), a simple yet efficient and effective adversarial attack in Black-box scenarios. Specifically, the cross-shaped patch consists of two line segments intersected and perpendicular to each other at the midpoint. These two line segments are designed to be sufficiently thin and long to reach the four corners of the input image nearly. Thus, the patch has a globalized perturbation capacity while preserving its continuousness. The content and location of cross-shaped patch are then iteratively optimized by a carefully contrived random search-based algorithm to maximize this global property. Comprehensive experiments are conducted on four benchmark datasets against various victim networks. The results show that the proposed CSPA outperforms the existing patch-based attacks regarding both attack success rate and query efficiency by a large margin. Specifically, compared with the baselines, CSPA increases the success rate by up to 20% on ImageNet and reaches 100% on the CIFAR-100 and CIFAR-10 datasets. Meanwhile, CSPA reduces the average number of queries by up to 7 times. Even for the white-box attack scenario, our designed cross-shaped patch can still be applicable, achieving state-of-the-art performance.